Presentation - González Sánchez, David (2021)
We describe the ideas of N°22 of Revista Perspectivas: Social Studies and Epistemology, in order to debate What History and Geographic to teach. Therefore, We study the discussion about Social Studies in the World and try to Understand the debate in Central America.